Evaluation of the yield, morphological and chemicals characteristics of varieties of purple corn (Zea mays L.) in the region Cajamarca-Peru - Rabanal-Atalaya , Melissa; Medina-Hoyos, Alicia (REVISTA TERRA LATINOAMERICANA, 2021)
Peru has a great diversity of agricultural products due to the variety of climates and geographical diversity, hence it accounts with seven main races of purple corn. Therefore, the objective of our research was to evaluate the yield, and the morphological and chemical characteristics of five varieties of purple corn, which were the following: INIA-601, MMM improved purple corn (experimental variety), UNC‑47, INIA‑615, and PM-581, plus Canteño race, which was used as control. The study was conducted at two altitudinal levels, 2770 m (Llollon) and 3140 m (Llanupacha), both belonging to the District of Ichocan, Province of San Marcos and Region Cajamarca in Peru, during 2017/18 and 2018/19 agricultural campaigns. The agronomic variables and anthocyanin content were evaluated. The results show that the best yield on average was for INIA-601, with 5.3 Mg ha-1 in Llanupacha and with 4.5 Mg ha-1 in Llollon. The varieties with the highest height of the plant and ear were MMM (2.33 and 1.2 m) and INIA-601 (2.35 and 1.25 m) in Llollon; whereas in Llanupacha, MMM (1.93 and 0.88 m) and INIA-601 (1.9 and 0.88 m), respectively, obtained the highest values. The INIA-615 variety showed the earliest flowering for females and males in both altitudinal levels, at days101.5 and 93.3 in Llollon and at days 125.6 and 118.3 in Llanupacha, respectively. In addition, this variety obtained the lowest percentage of rot in Llanupacha (2.3%) and in Llollon (5.9%). In addition, the INIA-601 variety was highlighted for having the highest quantity of anthocyanins in both the ear and bracts, presenting (6.7 and 7.5 mg g-1) and (2.9 and 2.5 mg g-1), in Llanupacha and Llollon, respectively.